Paghahanap ng ilaw sa gitna ng dilim an animation campaign on empowering paternal child care in the Philippines through the eyes of 10-14 year old children with migrant mothers from the C & D economic bracket - Are, Bianca Monique S.
As of 2007, with the growing population of migrant workers from the Philippines, 7 out of 10 children—or 10 million (Carandang, 2007), are beginning to grow up without their mothers, and non-traditional families begin to emerge through time. Although there is great attention on the effects of mother-child separations, there is a lack of emphasis on fathers who still play a great role in child rearing, especially when they are the ones left behind (Lam & Yeoh, 2016). Attention on this matter does not only redefine the concept of child-care, but it also redefines masculinity and the idea of gendered-relations.